Impacts of Phosphogypsum, Soluble Fertilizer and Lime Amendment of Acid Soils on the Bioavailability of Phosphorus and Sulphur under Lucerne (Medicago sativa) - Moussa Bouray; Jim Moir; Leo Condron; Niklas Lehto (Plants, 2020)
Legumes play critical dual roles in grazed grassland ecosystems; providing nitrogen inputs and high-quality feed for grazing livestock. However, many species fail to persist in acidic, low fertility soils. A glasshouse study was conducted to investigate the response of lucerne (Medicago sativa) to phosphogypsum (PG), lime and soluble P + S fertilizer (PS) application to two soils. Phosphorus and sulphur were applied through either PG (0, 1, 3 and 9 t ha−1) or P + S fertilizer at equivalent rates to PG. Both PG and PS were applied with or without lime, which was applied at 2 t ha−1. Yield and nutrient uptake of the lucerne was measured, while the soil was analyzed for pH, Olsen P and exchangeable aluminum. Yield responses were significantly different between the two soils. Maximum yields and P and S uptakes were obtained under PG 9 t ha−1 combined with lime. Exchangeable Al decreased in both soils under 1 ha−1 of PG compared with the control. At the highest rate, Olsen P increased by 8 and 6 mg kg−1 for PG and by 6 and 11 mg kg−1 for PS compared with the control for Glenmore and Molesworth soils respectively. Phosphogypsum showed positive effects on P and S bioavailability.